Gender Differences in the Spillover Between Romantic Experiences, Work Experiences, and Individual Adjustment Across Emerging Adulthood. (March 2014) - Shulman, Shmuel; Laursen, Brett; Dickson, Daniel J.
This study examines the interplay between negative romantic experiences, negative work experiences, and anxiety/depressive symptoms at three time points across ages 24–29 in a sample of 176 Israeli emerging adults. Males ( n = 96) and females ( n = 80) described different patterns of longitudinal spillover between work, romantic relationships, and well-being. For males, higher levels of negative romantic experiences predicted increases in negative work experiences, and higher levels of anxiety and depressive symptoms predicted increases in negative romantic experiences. For females, higher levels of negative work experiences predicted increases in later negative romantic experiences. For both males and females, higher levels of negative work experiences predicted later increases in anxiety and depressive symptoms. Findings of this study conducted on emerging adults align with existing research on work–family spillover and its effects on individual well-being.